Characterization of Sweet Pepper (Capsicum chinense) Collected in Venezuela - Jiménez, Rosa; Laurentin, Hernan Eduardo (New Countryside, 2025)
In Venezuela the term sweet pepper is referred to the species Capsicum chinense, very important vegetable in Venezuelan gastronomy. The objective of this study was to characterize morphologically a collection of Capsicum chinense, composed by accessions collected in Venezuelan home gardens, supermarkets, wholesale markets, familiar retail markets, enterprises and agricultural research institutions. Seeds from twenty five accessions collected from seven out of twenty three states in Venezuela were planted in field under a random complete blocks design with four replications, and twenty two morphological traits (vegetative and reproductive traits, including plant, stem, leaf, flower, fruit and seed traits) proposed by IPGRI descriptor were evaluated on a total of 20 plants per accessions. The most discriminant traits were related to the fruit, especially weight, color, shape of the apex, width, and shape. Principal components and phenogram were able to group similarly the 25 accessions based on the 22 morphological traits. No relationship between the statistical grouping and the geographical collection site was found. Broad morphological diversity found, especially at fruit-associated traits allows to project a comprehensive using of Capsicum chinense genetic resources, and therefore to assume future successful Capsicum chinense breeding programs in Venezuela to get new cultivars adapted to Venezue lan agro climatic and market conditions.